Governo interventorial e relações de poder na Paraíba pós-1930: A administração de Gratuliano Brito (1932 – 1934) - Sousa Neto, Bento Correia de (2016)
This research aims to assay the administration of the Intervener Gratuliano da Costa Brito (1932-1934) in the political and administrative centralization context and re-articulation of the political forces at the national and state levels after 1930. From this analysis we try to understand what were the measures taken by this Government in order to a reorganization of functional sectors in the State of Paraíba as well as political and social impact of these measures on the relationship between the state and local oligarchic forces. Despite the “Revolution" of 1930 has not resulted in profound changes in the current political structure in the First Republic, we understand that it led to significant changes in order to allow the rise of a modern-and-racional proposed model of national state. This process had been developed concurrently with a restructuring of the state administrative machinery that sought to track changes implemented nationwide. Therefore, our aim was to assess how this process occurred in Paraiba and what characteristics have been found throughout it . As a theoretical basis for our analysis we appropriate the contributions of New Political History, as well as the concept of Political Culture. Regarding the sources used we borrow the contributions of several authors who deal with the subject and the period in question, as well as handwritten and printed primary sources relating to the said Government (official documents , periodicals, reports , etc.) .